Relationship Between Sedentary Behavior and the Incidence of Constipation During the COVID-19 Pandemic - Elvira Sari Dewi; Bella Cendie Asteria; Yulian Wiji Utami (Journal of Nursing Science Update (JNSU), 2021)
The COVID-19 pandemic has caused changes in a variety of sectors, including education. Changes in online learning methods during the COVID-19 pandemic can increase the risk of sedentary behavior in students. Sedentary behavior is one of the factors related to constipation. This study aims to determine the relationship between sedentary behavior and the incidence of constipation during the COVID-19 pandemic in students at Universitas Brawijaya. This research is correlation research with a cross-sectional approach. Sampling used total sampling with a sample of 87 students according to the inclusion and exclusion criteria. Sedentary behavior was measured using the International Physical Activity Questionnaire – Short Form (IPAQ-SF) and the incidence of constipation was measured using the Constipation Scoring System (CSS). The correlation between sedentary behavior and the incidence of constipation was statistically analyzed using the Spearman Rank test with alpha=0.05. The results show that As many as 82.8% of students at Universitas Brawijaya have sedentary behavior and 17.2% are constipated. There was a correlation between sedentary behavior and the incidence of constipation (p=0.020; r=+0,249). In conclusion, there is a relationship between sedentary behavior and the incidence of constipation during the COVID-19 pandemic in students at Universitas Brawijaya.